PENGARUH CITRA MEREK DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN PADA PRODUK KOSMETIK - Wulandari, Rizky Desty; Iskandar, Donant Alananto (Jurnal Riset Manajemen dan Bisnis (JRMB) Fakultas Ekonomi UNIAT, 2018)
This research aimed to determine whether there is the influence of brand image and product quality towardsthe purchase decision of Cosmetic Products. This research uses quantitative method. The number of samples in this research was 100, this research used purposive sampling technique to determine the samples. Method of completion of data used in this research were a questionare and google form. Result of t test shows significant influence brand image variable on decision making with tcount 2,432 â‰¥ ttable 1.660. Significant influence product quality variable on decision making with tcount 5,693 â‰¥ ttable 1,660. Brand image and product quality variables simultaneously have an effect of purchase decision Keywords: brand image, product quality, purchase decision